PROGRAM MENCIPTAKAN MANFAAT BERSAMA UNTUK MENINGKATKAN PENDAPATAN PETANI PISANG DI KABUPATEN TANGGAMUS, PROVINSI LAMPUNG - Abdur Rofi (Analisis Kebijakan Pertanian, 2021)
The Creating Shared Value (CSV) program as an alternative to the Corporate Social Responsibility (CSR) program provides options that allow companies to increase competitiveness while stimulating inclusive growth in reducing the poverty of farming families. This study examines the CSV program by looking at farmers' interests and the impact of the CSV program on banana commodities in Tanggamus Regency, Lampung Province. This study uses primary data obtained from surveys of 60 partner and non-partner farmers and in-depth interviews with 18 people involved in the existing business model. This research was conducted in March-April 2020. The data were analyzed descriptively. The results showed that the CSV program had been implemented in the location. In this CSV program, farmers get assistance from the company and certainty of selling banana products at an agreed price. However, not all farmers are interested in the program for various reasons, including due to limited land, limited time available, and farmers who do not want to be bound by work agreements. The impact of the CSV program on the banana commodity on household farmers' income has not been significant because bananas are not the primary source of livelihood for household farmers. The policy implication is that the CSV program can be an alternative to CSR programs. However, the success of this program also needs to consider the profile and the sources of livelihoods of farmers to ensure that farmers' interest and involvement can be more optimal.